Exploring The Role Of Sharia Values In Shaping Customer Satisfaction And Word Of Mouth In Sharia-Compliant Hotels - Nita Selvia Rohmayati; Cepryana Sathalica Widyananda (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2025)
This study investigates the impact of the implementation of Sharia values on customer satisfaction and word of mouth (WOM) in Sharia-compliant hotels in City X. The research uses a quantitative approach with purposive random sampling, gathering data from 100 customers of Sharia hotels. Structural Equation Modeling (SEM) is used to analyze the relationships between Sharia values, customer satisfaction, and WOM. The findings indicate that the application of Sharia values positively influences customer satisfaction, and customer satisfaction in turn has a significant effect on WOM. Furthermore, customer satisfaction is found to mediate the relationship between the implementation of Sharia values and WOM. These results underscore the importance of aligning hotel services with Sharia principles to enhance customer satisfaction and foster positive WOM. The study offers practical insights for Sharia-compliant hotels to improve service quality and build stronger customer loyalty.